The Role of ESG Disclosure in Attracting Sustainable Investment in Indonesia’s Capital Market - Ramdhan, Dadan (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
Environmental, Social, and Governance (ESG) disclosure is increasingly recognized as a crucial driver of sustainable investment in capital markets, including Indonesia, where it is expected to enhance transparency, strengthen investor confidence, and direct financial resources toward companies with sustainable practices. Nonetheless, empirical realities show that many Indonesian corporations adopt a compliance-oriented approach, resulting in fragmented and inconsistent disclosures that limit the comparability and credibility of sustainability reports. This study employs a qualitative method with a library research approach, drawing on academic publications, regulatory documents, and corporate reports to analyze how ESG disclosure influences the attractiveness of sustainable investment. The findings indicate that regulatory frameworks established by the Financial Services Authority (OJK) and the Indonesia Stock Exchange (IDX) have provided an important foundation for institutionalizing ESG practices; however, implementation remains hindered by regulatory fragmentation, limited corporate capacity, and risks of greenwashing. ESG disclosure, while serving as a potential signaling mechanism for investors, has yet to fully function as a decisive factor in capital allocation due to uneven reporting quality and insufficient standardization. The study concludes that strengthening disclosure credibility through harmonized standards, enhanced monitoring, and capacity building is critical to advancing sustainable investment in Indonesia. Practically, these findings suggest that regulators, corporations, and investors must collaborate to improve the quality and reliability of ESG reporting, while academically, the study contributes to sustainable finance literature by highlighting gaps in sectoral practices, the integration of Islamic finance, and the role of technological innovations in enhancing ESG data verification.